Respuesta :

[tex]\text{Given that,}\\\\f(x)= \dfrac{x+1}{x-1}\\\\\\f'(x)=\lim\limits_{h \to 0} \dfrac{f(x+h) - f(x) }{h}\\\\\\ ~~~~~~~~=\lim\limits_{h \to 0} \dfrac{\left( \tfrac{x+h+1}{x+h-1}\right) - \tfrac{x+1}{x-1}}{h}\\\\\\~~~~~~~~=\lim\limits_{h \to 0} \dfrac{\tfrac{(x+h+1)(x-1) - (x+1)(x+h-1)}{(x+h-1)(x-1)}}{h} \\\\\\~~~~~~~~=\lim\limits_{h \to 0} \dfrac{\tfrac{x^2-x+hx-h+x-1 - x^2-xh+x-x-h+1}{(x+h-1)(x-1)}}{h}\\\\\\~~~~~~~~[/tex]

       [tex]~~~~~~~=\lim\limits_{h \to 0} \dfrac{\tfrac{-2h}{(x+h-1)(x-1)}}{h}\\\\\\~~~~~~~~=\lim\limits_{h \to 0} \dfrac{-2}{(x+h-1)(x-1)}\\\\\\~~~~~~~~=\dfrac{-2}{(x+0-1)(x-1)}\\[/tex]

       [tex]\\\\~~~~~~~~=\dfrac{-2}{(x-1)(x-1)}\\\\\\~~~~~~~~=\dfrac{-2}{(x-1)^2}[/tex]

ACCESS MORE